2012
DOI: 10.1186/2045-824x-4-18
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelial permeability and transendothelial migration of cancer cells by tropomyosin-1 phosphorylation

Abstract: BackgroundLoss of endothelial cell integrity and selective permeability barrier is an early event in the sequence of oxidant-mediated injury and may result in atherosclerosis, hypertension and facilitation of transendothelial migration of cancer cells during metastasis. We already reported that endothelial cell integrity is tightly regulated by the balanced co-activation of p38 and ERK pathways. In particular, we showed that phosphorylation of tropomyosin-1 (tropomyosin alpha-1 chain = Tm1) at Ser283 by DAP ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…35,36 Furthermore, we showed that endothelial cell permeability of ICG in vitro was promoted by both PGE 2 , a downstream product of COX-2, 33 and H 2 O 2 , an upstream reactive oxygen species of iNOS. 33,37 Prostaglandin E 2 is known to increase local blood flow, resulting in vascular hyperpermeability. 32 In the present study, intradermal injection of PGE 2 induced ICG permeability and accumulation in normal ear tissues, suggesting that enhanced permeability induced by PGE 2 was likely to be one of the mechanisms of tumor accumulation of ICG.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Furthermore, we showed that endothelial cell permeability of ICG in vitro was promoted by both PGE 2 , a downstream product of COX-2, 33 and H 2 O 2 , an upstream reactive oxygen species of iNOS. 33,37 Prostaglandin E 2 is known to increase local blood flow, resulting in vascular hyperpermeability. 32 In the present study, intradermal injection of PGE 2 induced ICG permeability and accumulation in normal ear tissues, suggesting that enhanced permeability induced by PGE 2 was likely to be one of the mechanisms of tumor accumulation of ICG.…”
Section: Discussionmentioning
confidence: 99%
“…Human recombinant CA‐I protein (Sigma) was added at 100 μmol/L to hCEC culture in vitro. Permeability across endothelial cell monolayers was measured using gelatin‐coated Transwell units (Boyden chambers) (6.5‐mm diameter, 0.4‐μm‐pore polycarbonate filter; Corning Costar), as previously described . Briefly, hCECs were plated at a density of 0.6×10 5 cells (or 1×10 5 in the case of transduced cells) per well (upper chamber) and were cultured for 3 days until a tight monolayer formed.…”
Section: Methodsmentioning
confidence: 99%
“…Permeability across endothelial cell monolayers was measured using gelatincoated Transwell units (Boyden chambers) (6.5-mm diameter, 0.4-lm-pore polycarbonate filter; Corning Costar), as previously described. 23 Briefly, hCECs were plated at a density of 0.6910 5 cells (or 1910 5 in the case of transduced cells) per well (upper chamber) and were cultured for 3 days until a tight monolayer formed. Endothelial permeability was determined by measuring the passage of FITC-labeled dextran (1 mg/mL of fluorescein isothiocyanate-dextran, molecular mass 40 kDa; Sigma-Aldrich) through the hCEC monolayer.…”
Section: Endothelial Cell Permeability and Apoptotic Deathmentioning
confidence: 99%
“…This protein is involved in the polymerization of the actin cytoskeleton and protects endothelial cell-cell junctions from the oxidative stress triggered by aqueous cigarette smoke extract 237 . TPM1 phosphorylation state regulates endothelial permeability to cancerous cells 238 , and TPM1 was also demonstrated to be a tumor suppressor in various cancers, including breast cancer 239,240 , where it resensitizes cancer cells to anoikis (programmed cell death triggered by detachment from the extracellular matrix). As SASH1 binds TPM1, it could be envisioned that it preserves endothelial integrity through the stabilization of the actin cytoskeleton.…”
Section: Figure 16 Mass Spectrometry Identification Of Sash1 Partnermentioning
confidence: 99%